COMPREHENSIVE ANALYSIS OF IMPORTANCE OF X-RAY INTERACTIONS WITH MATTER IN DIAGNOSTIC EXAMINATIONS - MOHAMMAD ABDULGHANI HAJOMAR, NEJAA NASSER ALHRBI, NAIF SALAH ALJOHANI, AWADAH RASHDAN ALHRBI, BANDER SALEH AL GOHANI, ABDALLAH RAJEH AL GOHANI, WAEL AYED ALAHMADI, TURKI AWADHALLAH T ALJABRI (Chelonian Research Foundation, 2022)
The X-ray interactions with matter are pivotal in the process, from the image quality to patient safety and the accuracy of the diagnosis. In this comprehensive analysis, the significant aspects of these probes are explored, ranging from their role in medical imaging to the mechanisms they involve, as well as the implications of this for diagnostic practice. This paper explains the connectedness of X-rays and biological tissues via literature review, method summarization, and results and findings substantiation. The main finding highlights the necessity of absorbing X-rays for precise diagnostics and improved clinical service. Further research and clinical applications are covered through recommendations as well. Keywords: X-ray, exposures, matter, radiological findings, medical imaginations.